Interactions of Root-Feeding Insects with Fungal and Oomycete Plant Pathogens - Willsey, Telsa; Chatterton, Syama; Cárcamo, Héctor (Frontiers in Plant Science, 2017)
Soilborne fungal and oomycete pathogens are the causal agents of several important plant diseases. Infection frequently co-occurs with herbivory by root-feeding insects, facilitating tripartite interactions that modify plant performance and mortality. In an agricultural context, interactions between pathogens, herbivores and plants can have important consequences for yield protection. However, belowground interactions are inherently difficult to observe and are often overlooked. Here, we review the impact of direct and indirect interactions between root-associated insects, fungi, and oomycetes on the development of plant disease. We explore the relationship between insect feeding injury and pathogen infection, as well as the role of insects as vectors of fungal and oomycete pathogens. Synergistic interactions between insects and phytopathogens may be important in weed suppression, and we highlight several promising candidates for biocontrol. Bridging the gap between entomological and pathological research is a critical step in understanding how interactions between insects and microorganisms modify the community structure of the rhizosphere, and how this impacts plant functioning. Furthermore, the identification of belowground interactions is required to develop effective pest monitoring and management strategies.